2020
DOI: 10.3389/fpsyg.2020.02011
|View full text |Cite
|
Sign up to set email alerts
|

A Robot Is Not Worth Another: Exploring Children’s Mental State Attribution to Different Humanoid Robots

Abstract: Recent technological developments in robotics has driven the design and production of different humanoid robots. Several studies have highlighted that the presence of human-like physical features could lead both adults and children to anthropomorphize the robots. In the present study we aimed to compare the attribution of mental states to two humanoid robots, NAO and Robovie, which differed in the degree of anthropomorphism. Children aged 5, 7, and 9 years were required to attribute mental states to the NAO ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 89 publications
5
80
0
3
Order By: Relevance
“…Several studies have shown that specific facial features (i.e., nose, eyes, and mouth) resembling human ones are particularly important for the perception of the robots' humanlikeness. [8][9][10][11] However, excessive resemblance to the human triggers the Uncanny Valley Effect: the more the appearance of robots is similar to humans, the more is the sense of eeriness. [12][13][14] The human sensitivity to the physical appearance of robots was also found in childhood, [15][16][17][18] in particular, children already at 5 years of age attribute greater mental qualities to a more anthropomorphic robot, that is, the NAO, compared to a more mechanical robot, that is, the Robovie.…”
Section: The Design Of the Hrss: Nao And Peppermentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that specific facial features (i.e., nose, eyes, and mouth) resembling human ones are particularly important for the perception of the robots' humanlikeness. [8][9][10][11] However, excessive resemblance to the human triggers the Uncanny Valley Effect: the more the appearance of robots is similar to humans, the more is the sense of eeriness. [12][13][14] The human sensitivity to the physical appearance of robots was also found in childhood, [15][16][17][18] in particular, children already at 5 years of age attribute greater mental qualities to a more anthropomorphic robot, that is, the NAO, compared to a more mechanical robot, that is, the Robovie.…”
Section: The Design Of the Hrss: Nao And Peppermentioning
confidence: 99%
“…[12][13][14] The human sensitivity to the physical appearance of robots was also found in childhood, [15][16][17][18] in particular, children already at 5 years of age attribute greater mental qualities to a more anthropomorphic robot, that is, the NAO, compared to a more mechanical robot, that is, the Robovie. 10 A recent study classified around 200 HSRs based on their level of human likeness. 19 In this collection, the NAO robot was rated on the human-like factor with a score of 46/100, while the Pepper robot with a score of 42/100.…”
Section: The Design Of the Hrss: Nao And Peppermentioning
confidence: 99%
See 1 more Smart Citation
“…Di Dio et al (2020b) shows that 3 years-old children tend to trust humans more than robots, as opposed to 7 years-old children. Manzi et al (2020) showed that children of 5, 7, and 9 years-old differently assign mental states to two humanoid robots, NAO and Robovie, differing on their level of anthropomorphism. It is possible that, for very young children under 3 years-old, the NAO robot may not be the most adequate tool (see Damiano et al, 2015, for a review of the different types of robots).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] However, there is still a long way to go in terms of technology to achieve these goals. Despite these technical limitations, several studies have shown that humans attribute human-like qualities to robots even in their current form [12][13][14][15][16][17][18][19] : this means that people have expectations of robots in terms of performance and interaction possibilities. However, a gap between people's expectations and actual technological advancements of robots could result in less effective human-robot interactions in the future.…”
Section: Introductionmentioning
confidence: 99%